Hydrogeochemical temporal variations related to the recent volcanic eruption at the Cumbre Vieja Volcano, La Palma, Canary Islands - Amonte, Cecilia; Melián, Gladys V.; Asensio-Ramos, María; Pérez, Nemesio M.; Padrón, Eleazar; Hernández, Pedro A.; D’Auria, L. (Frontiers in Earth Science, 2022)
From October 2017, and as a response to the occurrence of several seismic swarms on La Palma (Canary Islands, Spain), we strengthened the volcano monitoring of Cumbre Vieja system by carrying out periodic hydrogeochemical sampling at different points of interest. Two galleries -Peña Horeb (PH) and Trasvase Oeste (TO)- and one well -Las Salinas (LS)-, were selected with this objective. Significant temporal variations in pH, EC, ion content (HCO3-, F-, Cl-, Br-, SO42-, Na+, Ca2+ and Mg2+), partial pressure of carbon dioxide (pCO2) and isotopic signature of dissolved CO2 (δ13C-CO2) were observed throughout the study period. These changes observed in both chemical and isotopic composition were related to the interaction between deep volcanic fluids and the groundwaters and coincided with the occurrence of different seismic swarms leading to the final Tajogaite Volcano eruption occurred in Cumbre Vieja from September 19 to December 13, 2021. This work highlights the usefulness of monitoring the chemical and isotopic composition of groundwaters related to active volcanic systems, as they can provide important information about the magmatic gas input in the aquifers.